Letter - Barking Labour Party, Trades Council, NUR and organisations attached during crisis, n.d. (Barking)
1926-05-12 "Letter - Barking Labour Party, Trades Council, NUR and organisations attached during crisis, n.d." [g0174001.jpg], 3 - 12 May 1926, Barking Labour Party, Trades Council Local Organisation